Reliable and lightning‐safe monitoring of wind turbine rotor blades using optically powered sensors. Issue 2 (16th August 2016) - Worms, K.; Klamouris, C.; Wegh, F.; Meder, L.; Volkmer, D.; Philipps, S. P.; Reichmuth, S. K.; Helmers, H.; Kunadt, A.; Vourvoulakis, J.; Bett, A. W.; Koos, C.; et al.
Abstract: Blade condition monitoring systems with fiber‐optic sensors attract much attention because they are resistant to lightning strikes, a major issue with increasing blade lengths. However, fiber‐optic sensor systems are more complex and more expensive than their electronic counterparts. We describe a new blade condition monitoring system, which combines the lightning safety of optical fibers with the reliability and cost‐effectiveness of electronic sensors. The optical fibers transport data from the blades to the hub, and in addition, they provide the electrical power for operating the sensor units in the blades. To achieve full protection against lightning‐induced electromagnetic fields, an appropriate shielding of the sensor units is required. We present results on the reliability of a newly developed prototype based on optically powered sensors. In a field trial, the unit monitored successfully the blade vibrations of a 1.5 MW wind turbine for a period of 23 months. Copyright © 2016 John Wiley & Sons, Ltd.